Evaluation of Anti-ulcer Activity of Aqueous Extract Combretum paniculatum Vent in Mice and Rats using Acidified Ethanol-induced Ulcer Model - Builders, Modupe Iretiola (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2023)
The present study was carried out to investigate the anti-ulcer activity of 80% aqueous leaf extract of Combretum paniculatum (CP) in rats and mice. Various concentrations of CP aqueous extract (200, 400, and 800 mg/kg body weight) were used to determine the anti-gastric ulcer activities of methanol extracts of CP in mice and rats in an acidified ethanol-induced model. Cimetidine (150 mg/kg) was used as a reference drug. The following parameters, such as gastric fluid volume, PH, ulcer score, percentage ulceration, and percentage inhibition of ulcer index, were determined. An acute toxicity study was carried out, and the LD50 was determined as well as the histopathological study. Data were analyzed using one-way analysis of variance followed by a Tuckey post hoc test, and P < 0.05 was considered significant while P < 0.01 was considered highly significant. The CP aqueous extract highly significantly P < 0.01 reduced the gastric index by 41.8%, 51.3%, and 82.3% in the acidified ethanol-induced ulcer model with reference to the standard drug. The oral median lethal dose (LD50) was found to be >2000 mg/kg body weight. CP aqueous extract possesses both dose-dependent and time-dependent anti-ulcer activities. Bioactives such as flavonoids, tannins, phenols, alkaloids, terpenoids, glycosides, and steroids were present, while saponins were found to be absent. This study confirms the anti-ulcer pharmacological activities of CP aqueous extract; we suggest that further investigations should be carried out to isolate specific phytochemicals as well as to determine the mechanisms of action.